Does occlusal splint affect posture? A randomized controlled trial. Issue 4 (3rd July 2020) - De Giorgi, Ilaria; Castroflorio, Tommaso; Cugliari, Giovanni; Deregibus, Andrea
ABSTRACT: Objective: The aim of this study was to evaluate the effect of an occlusal splint on body posture of intra-articular temporomandibular joint (TMJ) disorders patients. Methods: The study was performed on 45 women affected by TMJ disorders divided into an occlusal splint group and a control group. Rasterstereographic recordings were performed at baseline and after 1, 3, and 6 months, in order to analyze the following postural parameters: trunk inclination, cervical and lumbar arrows, kyphotic and lordotic angles, trunk imbalance, pelvic tilt and torsion. Results: Regarding the postural parameters in the intragroup analysis, no significant differences were detected. The analysis between the two groups revealed significant differences concerning the cervical arrow, the kyphotic and lordotic angles. Discussion: Even if some differences were found between the control and the occlusal splint group, the low range of statistical significance made these results not significant from a clinical point of view.